A case report of incidentally elevated maternal serum alkaline phosphatase managed in a poor resource setting - Naik, Salonee Milind; Naik, Pornima Rajkumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
The normal serum concentration of alkaline phosphatase (ALP) in adults ranges from 47 to 147 IU/l. Alkaline phosphatase is known to be produced by syncytiotrophoblasts in the placenta during pregnancy. Its levels are normally increased in pregnant women and levels of up to twice the upper limit can be considered normal. There have been case reports pointing out that an abnormal rise in serum ALP levels could be a marker for placental insufficiency preterm delivery. Here we report a case with delivery of a normal infant and no placental pathology at term. There are very few reports of extreme elevations of ALP in a pregnancy without any co-morbidities and delivery of normal infant with a subsequent decline to normal after delivery. We present the case of a 23-year-old pregnant woman with an incidentally detected 10 fold elevated serum ALP which was managed at a sub district level hospital which is a poor resource setting. She was expectantly managed and delivered a healthy new-born with an unremarkable intrapartum and post-partum period. Her ALP levels were monitored during the peri-partum period and gradually declined. This case is important because it shows that an isolated increase in a biochemical marker can give a good feto-maternal outcome after expectant and vigilant management.